Influence of Husbands’ Attitudes Versus Knowledge on Maternal Breastfeeding Self-Efficacy Following Caesarean Section - ARI DEWANTI, ARI DEWANTI; Ivon Diah Wittiarika; Pudji Lestari (Universitas Airlangga, 2025)
Self-efficacy predicts a mother’s decision to breastfeed, the level of effort invested in breastfeeding, and the responses to challenges faced during the process. This study aims to determine the relationship between a husband’s knowledge and attitude towards exclusive breastfeeding and the self-efficacy of mothers who have undergone cesarean sections. The design of this research is correlational with a cross-sectional framework. The sample consisted of 38 mothers post-cesarean section and their husbands, obtained through a Non-Probability Sampling technique using sequential sampling in the Al Aqsha 4th room of Haji Hospital, East Java Province. The analysis in this study employs Spearman’s rho. The instrument assessed husbands’ knowledge and attitudes regarding exclusive breastfeeding and the short form of breastfeeding self-efficacy (BSE-SF). The study results indicated that the knowledge level of most husbands fell into a suitable category, at 89.5%. Most husbands exhibited positive attitudes, at 65.8%. Meanwhile, the majority of post-cesarean section mothers recorded high levels of breastfeeding self-efficacy, at 78.9%. The results of the Spearman rho test regarding the knowledge and self-efficacy of breastfeeding mothers following cesarean sections yielded p=0.141 (>0.05). In contrast, the relationship between husbands’ attitudes and the self-efficacy of breastfeeding mothers post-cesarean section was p=0.022 (<0.05). While the knowledge and attitudes of husbands regarding exclusive breastfeeding are categorized mainly as good, their knowledge does not influence the self-efficacy of mothers breastfeeding after cesarean delivery.